Political communication strategy in the 2024 indonesia’s presidential election - Erman Anom; Elisabeth Vina; Mus Chairil Samani (Penerbit Universiti Kebangsaan Malaysia, 2024)
In every election, candidates employ various techniques to communicate their mission and vision to their respective voters. Winning an election depends on how good the candidate employs the various tools of communication, using both traditional mass media and social media. This research examines the political communication strategy used by Anies Baswedan during the Indonesian Presidential Election 2024. The objective of this research is to study the political communication style used by Anies Baswedan as a non-party political leader in garnering public support and winning the Presidential Elections. All the other presidential candidates contesting in the election are representing various political parties. All the feeds that were published in his Instagram account during the election were analysed. The analysed data is later triangulated with data from key informants to get an insight on Anies Baswedan’s political thoughts. Data from the Instagram account indicates that his team of communicators employs hashtags, news feed, political ads and visual styles to increase awareness among his voters, in the hope of influencing his voters. The various content published is found to be relevant and significant with the voters but is insufficient to win an election. Although he run initially as a non-political party candidate before gaining endorsement from a political party to run for President, he lost could be due to the lack of political infrastructure support that is needed to ensure his words spread throughout vast Indonesia archipelago.